Three half-sandwiched iron(II) monocarbonyl complexes with PNP ligands: Their chemistry upon reduction and catalysis on proton reduction. (20th November 2022) - Natarajan, Mookan; Li, Xueming; Zhong, Wei; Wang, Wei; Xiao, Zhiyin; Jiang, Xiujuan; Lu, Chunxin; Liu, Xiaoming
Highlights: The 19e-species generated from one-electron reduction undergo isomerisation by cleaving one of the two Fe−P bonds. The isomerisation is slowed down by a H-π interaction in the 19e-species between one of the phenyl rings and the benzylic moiety. Presence of CO accelerates the isomerisation to form CO-adducts, [Fe(I)Cp(CO)2 ( m -L1–3 )]. The cyclohexyl group greatly enhances the electron density of the iron center and cause significant PCET effect in proton reduction catalysed by the complex (1 + ). Abstract: Three half-sandwiched iron(II) monocarbonyl cationic complexes (1 + −3 + ) containing a azadiphoshine ligand (PNP, L1 – 3 ) and an iodide as the counter anion, [Fe(II)Cp(CO)(L1 – 3 )]Ι (Cp =  η 5 -cyclopentadienyl; L1  = Ph2 PN(cyclohexyl)PPh2, 1 + ; L2  = Ph2 PN(phenyl)PPh2, 2 + ; L3  = Ph2 PN(benzyl)PPh2, 3 + ) were reported. All the complexes were fully characterized, of which complexes 2 + and 3 + were crystallographically analysed to confirm their "piano stool" geometry. Electrochemically, complexes 1 + −3 +  exhibited two major reduction events at about −1.9 V and −2.3 V, respectively, assigned to Fe(II) → Fe(I) and Fe(I) → Fe(0), respectively. The first reduction produces a 19e-species, [Fe(I)Cp(CO)(L1 – 3 )] (1, 2, and 3 ) whereas the second event is not assigned to the further reduction of the 19e-species but a 17e-intermediate ([Fe(I)Cp(CO)( m -L1 – 3 )]; 1′, 2′ and 3′ ) which is chemically generated from the 19e-species by cleaving one of the two Fe−P bonds. However, the 19e-species 3 is considerably more stable than the other two analogues (1 and 2 ) due to H− π interaction between the ortho -H atoms from one of the four phenyl rings on the phosphine atom and the phenyl ring of the benzyl group as revealed by theoretic calculations. Therefore, species 3 is stable enough for the reduction of 3  → 3 − to be electrochemically detected right before the second major reduction. To further shed some light on the electrochemical mechanism, both bulk electrolysis and chemical reduction of complexes 1 + −3 +  with cobaltocene as the reducing agent were conducted. Under N2 atmosphere, the neutral 17e-species, [Fe(I)Cp(CO)( m -L1 – 3 )] (1′ -3′ ) was spectroscopically detected whereas under CO atmosphere, CO-adducts, [Fe(I)Cp(CO)2 ( m -L1 – 3 )], were generated. The formation of CO-adduct explains the loss of reversibility of the first reduction (3 + ) under CO atmosphere in its electrochemistry. With acetic acid as the proton source, only the second major reduction of the complexes exhibited significant catalytic activity, of which complex 1 + possessed the best performance. Significant proton-coupled electron transfer (PCET) effect was observed for complex 1 + due to the strong electron-donating capability of the ligand (L1 ). Graphical abstract: Image, graphical abstract